2018
DOI: 10.3390/antibiotics7040098
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloid-Rich Crude Extracts, Fractions and Piperamide Alkaloids of Piper guineense Possess Promising Antibacterial Effects

Abstract: Piper guineense is a food and medicinal plant commonly used to treat infectious diseases in West-African traditional medicine. In a bid to identify new antibacterial compounds due to bacterial resistance to antibiotics, twelve extracts of P. guineense fruits and leaves, obtained by sequential extraction, as well as the piperine and piperlongumine commercial compounds were evaluated for antibacterial activity against human pathogenic bacteria. HPLC-DAD and UHPLC/Q-TOF MS analysis were conducted to characterize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 42 publications
2
6
0
Order By: Relevance
“…This is the first report regarding the combined actions of selected alkaloids on cancer cell lines. In turn, the results obtained for PL and SAN individually are confirmed by literature reports that present a wide spectrum of activities of the above-mentioned natural compounds [10,41,49]. Besides, the clinical potential of the alkaloids may be demonstrated by the possibility of PL and SAN applications in the forms of combined therapies with conventional cytostatics.…”
Section: Discussionsupporting
confidence: 76%
“…This is the first report regarding the combined actions of selected alkaloids on cancer cell lines. In turn, the results obtained for PL and SAN individually are confirmed by literature reports that present a wide spectrum of activities of the above-mentioned natural compounds [10,41,49]. Besides, the clinical potential of the alkaloids may be demonstrated by the possibility of PL and SAN applications in the forms of combined therapies with conventional cytostatics.…”
Section: Discussionsupporting
confidence: 76%
“…From the study, methanolic and aqueous extracts of Piper guineense and Gongronema latifolium have concentration dependent antimicrobial activity on the test organisms; Staphylococcus aureus and Escherichia coli. This is in agreement with the findings ofMgbeahuruike et al (2018).The organisms (Staphylococcus aureus) were sensitive to methanolic extract of Piper guineense at the highest concentration of 10mg/ml with inhibitory zone of 10mm but had no inhibitory effect on Escherichia coli at same concentrations. This observation is consistent with a previous research byMgbeahuruike (2019), who reported the methanolic extract of Piper guineense to have inhibitory effect of 14.7mm on Staphylococcus aureus.…”
supporting
confidence: 92%
“…Tetracycline hydrochloride (Sigma-Aldrich, St. Louis MO, USA), rifampicin (Sigma-Aldrich), and itraconazole (Sigma-Aldrich) were the antibiotics used in the investigation. The selection of tetracycline, rifampicin, and itraconazole was based on their activity against bacterial and fungal strains in a previous study [34]. S. aureus American Type Culture Collection ATCC 25923, P. aeruginosa ATCC 27853, and C. albicans ATCC 10231 cultures used in this investigation were obtained from the Division of Pharmaceutical Biosciences, Faculty of Pharmacy, University of Helsinki, Finland.…”
Section: Methodsmentioning
confidence: 99%